Influence of Corporate Governance Practices on Public Sector Sustainable Development in Nepal - Yadav, Bivek Kumar; Neupane, Pushkar; Sah, Kishan; Rawat, Ramesh (Nepalese Journal of Finance, 2025)
The study examines the influence of corporate governance practices on public sector sustainable development in Nepal. Return on assets and earning per share are selected as the dependent variables. The selected independent variables are board size, audit committee size, number of board meetings, female directors, independent directors, and institutional ownership. The study is based on secondary data of 12 commercial banks with 108 observations for the study period from 2014/15 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance practices on public sector sustainable development in Nepal. The study showed that board size has a positive impact on return on assets and earning per share. It indicates that increase in board size leads to increase in return on assets and earning per share. Similarly, audit committee size has a positive impact on return on assets and earning per share. It indicates that increase in audit committee size leads to increase in return on assets and earning per share. Likewise, number of board meetings have a positive impact on return on assets and earning per share. It indicates that increase in board meetings lead to increase in return on assets and earning per share. However, female directors have a negative impact on return on assets and earning per share. It indicates that increase in proportion of female directors on board leads to decrease in return on assets and earning per share. Further, independent directors have a negative impact on return on assets and earning per share. It indicates that presence of independent directors in the board lead to decrease in return on assets and earning per share. Moreover, institutional ownership has a positive impact on return on assets and earning per share. It indicates that higher the institutional ownership, higher would be the return on assets and earning per share.